The post-war transformation of West Germany's economy: A model for the GDR? - Dieter Lösch (Intereconomics, 1990)
The unification of the two German states within a relatively short period of time now appears inevitable. Yet there is no historical precedent for a successful transformation from a socialist to a market economy. Doubts have been voiced by some as to whether such a transformation is possible. The following article compares the situation facing the GDR today with that facing the Federal Republic in 1948 and examines the conclusions to be drawn from this comparison.
Keywords: 330; GDR